Do default assignments increase savings of the poor? Empirical evidence - Eva Haaser; Melanie Koch (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Although households in developing and emerging countries are relatively poor, there is potential to save. For example, one study estimates that up to 8.1% of a poor household's budget in such countries is spent on so-called temptation goods, like alcohol, tobacco, and festivals (Banerjee and Duflo, 2007). At the same time, many households are aware of the fact that they do not save enough. They name factorslike self-control problems and family obligations as reasons why they cannot save more. In high income countries, default assignments already facilitate decision making in many areas of life. Among others, these could not just successfully increase organ donation rates (Johnson and Goldstein, 2003) but also retirement savings (Thaler and Benartzi, 2004). With the increased supply of formal financial services in the developing world, default assignments are also a romising and costeffective tool for these households. Prominent studies on whether and how default assignments increase the savings of the poor are summarized below.
Keywords: 330